Analysis of Service Quality of Investment and One Door Integrated Service Department of Penajam Paser Utara Regency - Katriani, Ariska Nova; Hamid, Muliyadi; Suyuthi, Nurmadhani Fitri (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
This research aims to analyze community perceptions of the quality of services provided by the Investment and Integrated One-Stop Service Agency of Penajam Paser Utara Regency. The research focuses on five key dimensions of service quality: tangible, reliability, responsiveness, assurance and empathy, with the goal of understanding how each dimension affects public satisfaction with the provided licensing services. The research offers a comprehensive overview of community experiences and identify things that need improvement to enhance overall service quality. The methods used in the research is a descriptive qualitative approach, utilizing in-depth interviews with 50 respondents to collect data. The gathered data were analyzed using an interactive model, which involves categorization and interpretation to identify major themes in community perceptions of the service. This technique provides a deeper understanding of the factors influencing service quality and how these aspects are perceived by the public. The results indicate that, overall, the community has a positive perception of the services provided by the Agency is mean DPMPTSP, particularly in terms of reliability and the professionalism of the staff. However, there are things requiring improvement, such as inadequate facilities and a lack of efficient digital resources. Responsiveness to community feedback is also noted as a things that need enhancement. The research provides concrete recommendations for improving facilities, enhancing responsiveness, and developing digital information systems to increase the overall quality of services.